(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
Local or regional elections have taken place in Russia during the United Voting Day, on 8 September 2019. The chronicle analyses the results of these last administrative elections, gives an overall picture of the development and the assessment of the party system and highlights the new political scenario in which the new election cycle, from 2019 until 2021, will be held